(untitled) (Journal of Special Education and Rehabilitation, 2013)
On 22nd of December 2012 the Macedonian Scientific Society for Autism (MSSA) together with the Rotary Club Skopje - Cyril and Methodius organized a New Year party for children with autistic spectrum disorder. The party was held in the playground Astera in Skopje, Taftalidze, and lasted for about 2 hours. The party was attended by 34 children with autistic spectrum disorder together with their siblings. Because the majority of children were on gluten free diet, there were packets with extensive educational material and specialized toys for them and a convenient number of packets with similar content was provided for their siblings. As a part of the program was the inevitable Santa who, according to the scenario, appeared at one point of time and gave the packets to the children. From obvious reasons, personal, technical and spatial, there was no opportunity for the media with photo and video cameras to be present at the celebration. It is also in the interest of fulfilling the parents’ desire for anonymity. But Rotary Club provided video and photo documentation already set available on online platforms ("Facebook" "Youtube" the website MSSA: www.mssa.org.mk). It should be noted that the Rotary Club Skopje - Cyril and Methodius conducts a project for aiding and socialization of children with autism in the Republic of Macedonia. The entire project, from the outset is conducted in full cooperation and coordination with the members of the MSSA.